Individual social capital and migration - Julie L. Hotchkiss; Anil Rupasingha (Federal Reserve Bank of Atlanta, 2018)
This paper determines how individual, relative to community, social capital affects individual migration decisions. We make use of nonpublic data from the Social Capital Community Benchmark Survey to predict multidimensional social capital for observations in the Current Population Survey. We find evidence that individuals are much less likely to have moved to a community with average social capital levels lower than their own and that higher levels of community social capital act as positive pull-factor amenities. The importance of that amenity differs across urban/rural locations. We also confirm that higher individual social capital is a negative predictor of migration.
Keywords: R23; D71; C36; C38; 330; social capital; migration; Current Population Survey; amenities; nonpublic data; factor analysis